Human Development Index, Liquidity Risk, Credit Risk and Financial Performance of Rural Credit Institutions in Bali - Muliartha RM, Ketut (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020)DO - 10.24843/JIAB.2020.v15.i02.p08, 2020)
Research aims to analyse the strategic role of rural credit institutions (LPD) in realizing the independence of society. Research using human development index variables, the ratio of loan to deposit, the ratio of quality of earning assets to see the impact on the financial performance of LPD as measured by return on Asset. The research sample is 305 units of LPD financial performance. The results of the study showed asset value, positive impact on the LPD's instability.  The risk of credit and liquidity risk negatively impacts the LPD's instability. The higher the Human Development Index, the development of LPD is increasingly positive seen from the total value of managed assets. Keywords:  Human development Index, liquidity risk, credit risk, financial performance, asset earning.